Is there an association between female circumcision and perinatal death? - Essén Birgitta; Bödker Birgit; Sjöberg N-O; Gudmundsson Saemundur; Östergren P-O; Langhoff-Roos Jens (The World Health Organization, 2002)
OBJECTIVE: In Sweden, a country with high standards of obstetric care, the high rate of perinatal mortality among children of immigrant women from the Horn of Africa raises the question of whether there is an association between female circumcision and perinatal death. METHOD: To investigate this, we examined a cohort of 63 perinatal deaths of infants born in Sweden over the period 1990-96 to circumcised women. FINDINGS: We found no evidence that female circumcision was related to perinatal death. Obstructed or prolonged labour, caused by scar tissue from circumcision, was not found to have any impact on the number of perinatal deaths. CONCLUSION: The results do not support previous conclusions that genital circumcision is related to perinatal death, regardless of other circumstances, and suggest that other, suboptimal factors contribute to perinatal death among circumcised migrant women.